Non-dysraphic Subpial Intramedullary Lipoma of Cervicothoracic Spine - Hamal, Aliza; Karki, Anjan Singh; Gurung, Ashim; Shrestha, Dipendra Kumar; Shilpakar, Sushil Krishna (Nepal Journal of Neuroscience, 2021)
Intramedullary spinal cord tumors are rare and comprise less than one percentage of all central nervous system (CNS) neoplasms. When encountered, most are found in the lumbosacral region with coinciding spinal dysraphism. Here, we discuss a case of isolated non-dysraphic intramedullary lipoma of cervicothoracic spine in an adolescent who was surgically managed with posterior decompression and subtotal resection via laminoplasty.A 21-year-old male adolescent, without a history of spinal dysraphism, presented with a progressive sensory ataxia. This manifestation was attributed to magnetic resonance documented intramedullary lipoma, extending from C7 to T2 spinal level. Patient underwent subtotal surgical resection of the lesion; and histopathology report was confirmed as spinal lipoma.Surgical management of this rare pathology has a wide variety of options depending on clinical presentation. In our case, a subtotal resection and laminoplasty was achieved with no further worsening of neurologic symptoms.